PENGARUH TRIAL BY THE PRESS TERHADAP PENEGAKAN HUKUM PIDANA DI INDONESIA - Pardede, Sonora Gokma; Nelson, Febby Mutiara (Faculty of Law, Universitas Pasundan, 2023)
Press coverage on criminal news has allegedly conducted trial by the press. Media seems to take the role as law enforcement by searching for evidence, interviewing witnesses, analyzing the case and at the end judging based on their opinion towards the criminal case. Trial by the press certainly contradict the principle of presumption of innocence and the fair trial. Trial by the press often found when reporting the news of murder case of Brigadier Yosua and the domestic violence case of Valencya. This research studied about the impact of trial by the press on the process of criminal law enforcement in Indonesia and how the media covers the criminal case to avoid trial by the press. The research method used is juridical normative with conceptual analysis, statute approach and case analysis. The findings of the research are that trial by the press resulted in trial by the public where people conclude their own judgment of one particular case. Post entry into force of the New Penal Code, alleged media conducting trial by the press is subject to imprisonment and fine under Article 281 of the New Penal Code Keywords: Trial by The Press, Pers, Presumption of Innocent, Fair Trial.